PERANCANGAN GAME VISUAL NOVEL FOLKLOR MITOS HORROR NUSANTARA DENGAN MENGGUNAKAN PENDEKATAN MDA FRAMEWORK - Saefudin, Ahmad Thabathaba'i; Putra, Ricky Widyananda; Misky, Fatma (Kartala, 2024)
The abundant cultural richness of Indonesia has bestowed a variety of myths, legends, and folk tales that have been cherished heritage from generation to generation. Nusantara folklore and myths offer captivating and mysterious stories, often intertwined with the supernatural, ghosts, or mystical creatures. However, with the increasing influence of foreign cultures, there is a pressing need to uplift and preserve the cultural heritage of Nusantara. In the entertainment industry, the horror genre has gained popularity, especially in the gaming world, whether in action games, adventures, or interactive stories like visual novels. Horror games provide thrilling and suspenseful experiences, combining strong atmospheres and narratives to create an eerie ambiance. Therefore, the horror genre is utilized in the design of this game to deliver captivating and adrenaline-inducing experiences for players. The visual novel approach is employed to enable players to immerse themselves in Nusantara folklore and horror myths. In the game design process, the MDA Framework approach is used as the primary guideline. The MDA Framework divides the gaming experience into three main components: mechanics, dynamics, and aesthetics. This approach ensures harmony between game rules, player emotional responses, interactions, and the overall impression desired in terms of visual presentation, atmosphere, and conveyed messages. It is hoped that a consistent and satisfying gaming experience can be created for players, while simultaneously introducing them to the myths, folklore, and cultural richness of Nusantara.